(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This project Phonocardiography and analysis using standard deviation profile was complete in Dhaka, Bangladesh, October-2013 and the models were randomized to thirty cases. This project gives a brief idea on heart signal processing by using the method of phonocardiography. A digital stetescope was used to pick up the heart sounds from different patients and the corresponding analysis was performed. The project mainly attempts the use of standard deviation profile in heart rate calculation instead of the existing shanon energy profile at noisy environments. The project also emphasizes on the heart signal analysis using cheap and simple hardware and highly sophisticated use of software.Considering the results, the SureShrink algorithm is seen to provide the best performance the LMS-ALE algorithm resulted in an HS recovery of 91- 93% with 89-92% noise reduction. RLS-ALE turned up 95-97% HS recovery with 90-92% noise reduction.